The Analisis Return On Asset, Return On Equity, dan Net Profit Margin dalam Memprediksi Pertumbuhan Laba Pada Perbankan Terdaftar di Bursa Efek Indonesia (BEI) - Arisky Andrinaldo; Eri Triharyati; Ade Famalika; Indrawati Mara Kesuma (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The problem in this research is the increase and decrease in profit that occurs in the variables ROA, ROE, NPM, and profit growth. This study uses data collection method is documentation on banking companies on the Indonesia Stock Exchange. The results show that Hypothesis 1 that ROA has a significant effect on Profit Growth, This means that when there is an increase in ROA, it has an effect on Profit Growth. Hypothesis 2 that ROE has no significant effect on Profit Growth, this is because the significance value is 0.038 <0.05. Hypothesis 3 that NPM has a significant effect on Profit Growth, then NPM will affect the expected profit growth of the owner on net income from company income. Hypothesis 4 shows the results that ROA, ROE and NPM have a significant effect on Profit Growth. The Fcount obtained is 3.270 with a significant level of 0.034 meaning that the level is significantly less than 0.05 or goodness of-fit so it can be concluded that simultaneously (simultaneously) all independent variables have a significant effect on the dependent variable.